Mandibular Splint: Correction of Jaw Deviation following Hemimandibulectomy - R K Karna; D K Vijaykumar; R V Kanade; T Cherian (Indian Journal of Plastic Surgery, 2000)
Nineteen patients who underwent hemimandibulectomy with PMMC flap reconstruction as a part of the treatment for residual or recurrent oral cancer following radical radiotherapy participated in the study. Sixty eight percent of the patients vv-ere edentulous. The parameters measured during follow-up included the degree of correction of deviation, cosmetic appearance & patient satisfaction. Complete correction of jaw deviation was achieved in eight patients. In five patients, the deviation was partially corrected but the patients were not satisfied with the cosmetic appearance. In one case no change was observed. The mandibular splint was found to be a useful tool for the correction of jaw deviation following hemimandibulectomy, especially in edentulous patients.